Development communications through forum in participation and motivation of village communities in Indonesia - Dwinarko, Dwinarko; Sjafrizal, Tabrani; Widodo, Aan; Muhamad, Pagi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The public's perception of development in the era of digitalization and the current global village provides a motivational meaning for the participation of citizens as a whole and government administrators. This study aims to determine the perceptions and motivations of the community in village development meetings. The research approach used is descriptive-qualitative with narrative analysis based on the results of interviews with informants. The results of the study show that participating in development can provide motivation and obtain a common opinion that refers to the information conveyed by the leadership so that they are more enthusiastic about carrying out development. The motivation for community involvement places more emphasis on the decision-making process in community institutions—participation as a form of community emancipation in the process of involvement in infrastructure and economic development planning. The contribution of this research in theory can provide knowledge about the common perception of the community that deliberation is an effective model of communication in development communication.Recommendation: Subsequent research is on social construction regarding gender equality, village apparatus, and village institutions in the motivation of village development meetings.